PERANCANGAN APLIKASI PEMANTAUAN PRESTASI ATLIT DAN PENERAPAN METODE MOORA UNTUK PENERIMAAN BEASISWA ATLIT TEMBAK PERBAKIN - Nito Alif Briantoro (CV. Multi Kreasi Media, 2024)
Shooting sport is one of the canag sports that is enjoyed by many people. One of the most popular shooting sports clubs even has branches in various regions, namely Perbakin. Perbakin has a lot of shooting athletes who have quite a lot of achievements. In this study, the author describes the design of an application for monitoring athletes who use the Moora method. The MOORA method is a decision support system, in this study using the Multi-Objective Optimization by Ratio Analysis (MOORA) method to determine athlete acceptance at a shooting club. The MOORA method is used to calculate the weight value of each attribute, the ranking process will select alternative shooting athletes in the refinery, from all available alternatives according to predetermined criteria based on the results of calculating the highest value.